KEBIJAKAN PENGELOLAAN HUTAN, KEMISKINAN STRUKTURAL DAN PERLAWANAN MASYARAKAT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The implementation of various forest management policies by government often fails to proteCt forest and reduce the number of poor communities around it. This study aims tofind out discrimination in forest management policy issued and implemented by State, the resultant structural poverty, and social resistance done by communities within and around the forest conservation area. This study was a qualitative study with both descriptive analytical approach conducted at a State level and Husserl's phenomenology at an individual level and Berger at collective level. The location of the study was Atar Lebar Village in Forest Conservation Area of TNBBS West Lampung Regency. The results of the study indicate that the logging done by the local community was due to their displeasure against the government policy to be discriminatory between timber company and community. Solution that should be given to the socio-structural problems of Atar Lebar area is the implementation of deliberative policy to resolve conflicts between the government and Atar Lebar in forest conservation area ofTNBBS. Keywords: Policy, Poverty, Social Resistance